O DIREITO DE RESISTÊNCIA À OPRESSÃO E OS POVOS INDÍGENAS EM MATO GROSSO DO SUL: UMA ANÁLISE SOB A PERSPECTIVA DO PLURALISMO JURÍDICO - Adriana de Oliveira Rocha (2020)
The legitimate use of the right of resistance to oppression, as coined in the Declaration of the Rights of man and of the Citizen, in France of 1789, is the subject of the science of Law and philosophy for several centuries, before and after the declaration. This research discusses this right from the perspective of indigenous peoples in the state of Mato Grosso do Sul, the federated unit that has the second largest contingent in the country, and high levels of human rights violations in relation to them. It is also studied the concept of legal alienation, which is that definer of the denial of rights to certain social groups even though formally the legal provisions should protect them. At the same time, it is observed the existence of rules of conduct among indigenous people, which would be identified with the so-called legal pluralism. Does this own way of existing, self-determining, and obeying the proper rules of conduct induce the overcoming of the state of legal alienation through the right of resistance? Here's the problem of the research. This is a descriptive and exploratory deductive research, in which the bibliographical and documentary methods are used, with the objective of identifying in the indigenous actions documented in manifests, public notes, letters, dissertations and academic theses, books and press news, the exercise of the right of resistance to oppression as described in the philosophical and juridical literature, and ruled in some international documents and constitutions of democratic countries. The research comes to the conclusion that, although not formally used as the basis of the sul-mato-grossense indigenous movement, the right of resistance to oppression has been practiced by the indigenous people in their actions to recover areas of traditional occupation, obtain the implementation of public policies of education and health, and to position itself politically before the state powers, so as to maintain its cohesion and existence as an ethnically differentiated population, all with the sense of overcoming the state of legal alienation.